Vibration Measurement of a Screening Machine - Rónai, László; Lénárt, József; Szabó, Tamás (International Journal of Engineering and Management Sciences, 2020)
In this paper we use linear vibration approach to make a model of a horizontal vibration screen, which can be applied at gravel pit in order to perform separation operation of the wet gravel particles. The model can produce the natural frequencies of the system, which are useful in the adjustment of the angular velocity of the vibration exciter. A laser triangulation unit is well applicable to measure peak-to-peak amplitude of the working vibration screen. Comparison has been performed between the results of the simulation and the measurements.